2019
DOI: 10.3390/ijms20030554
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Fucoidan Alleviate Acceleration and Exacerbation of Hippocampal Neuronal Death Following Transient Global Cerebral Ischemia in High-Fat Diet-Induced Obese Gerbils

Abstract: Fucoidan, a natural sulfated polysaccharide, displays various biological activities including antioxidant properties. We examined the neuroprotective effect of fucoidan against transient global cerebral ischemia (tGCI) in high-fat diet (HFD)-induced obese gerbils and its related mechanisms. Gerbils received HFD for 12 weeks and fucoidan (50 mg/kg) daily for the last 5 days during HFD exposure, and they were subjected to 5-min tGCI. Pyramidal cell death was observed only in the CA 1 area (CA1) of the hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…In addition, it has been reported that a severer aspect of neuronal loss/death in the hippocampus is shown following 15 min of TFI than that in 5 min TFI in gerbils [ 2 ]. Furthermore, a rat model of focal brain ischemia induced by MCAO for over 1 h develops infarct lesion (necrotic tissue) which is easily visualized by 2, 3, 5-triphenyltetrazolium chloride (TTC) assay, but infarction does not occur in the brain induced by TFI for 5–15 min in gerbils when the TTC assay is applied, in which selective neuronal death only occurs [ 1 , 15 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that a severer aspect of neuronal loss/death in the hippocampus is shown following 15 min of TFI than that in 5 min TFI in gerbils [ 2 ]. Furthermore, a rat model of focal brain ischemia induced by MCAO for over 1 h develops infarct lesion (necrotic tissue) which is easily visualized by 2, 3, 5-triphenyltetrazolium chloride (TTC) assay, but infarction does not occur in the brain induced by TFI for 5–15 min in gerbils when the TTC assay is applied, in which selective neuronal death only occurs [ 1 , 15 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The direct method is to analyze the in situ production of superoxide anion by DHE fluorescence assay [ 11 , 41 ]. The indirect method is to quantify end-products generated by ROS via 4-HNE immunohistochemistry for lipid peroxidation [ 30 , 42 ]. In our current study, the excessive production of ROS and increased lipid peroxidation in the CA1 pyramidal cells was examined following 5 min TFI, whereas the pretreatment with 30 mg/kg CGA remarkably attenuated them, showing that SOD expressions were significantly increased in the CA1 pyramidal cells before and after TFI.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight, blood glucose and serum lipid were measured at 12 weeks after ND or HFD according to our previously published method [ 30 ]. Briefly, the gerbils were deeply anesthetized by intraperitoneal injection of pentobarbital sodium (60 mg/kg) (JW Pharmaceutical, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral ischemia in gerbil study revealed that there were elevated levels of OS indicators (dihydroethidium and 8-hydroxyguanine (8-OHdG)) and reduced levels of antioxidant enzymes (superoxide dismutase (SOD1) and SOD2) in the obese gerbils compared to nonobese, both in pre-and postischemic phases. But this obesity-induced oxidative damage could be attenuated by pretreated fucoidan which had antioxidant properties [83]. In CHD, research suggests that obese patients with myocardium are more susceptible to ischemia compared to nonobese people, with enhanced levels of ROS and ROS-producing enzymes (i.e., p47phox, xanthine oxidase) and reduced antioxidant activity (mitochondrial aldehyde dehydrogenase and heme oxygenase-1) [84].…”
Section: Oxidative Stress and Risk Factorsmentioning
confidence: 99%